Animal Protection in Light of Modern Legal Thought and Islam Law’s Perspective - Saqib Jawad (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2025)
Abstract: Animals possess certain rights like human beings, including the right to life, liberty, health, well-being and reasonable abode. So far, only the right to life of animals has been given due consideration; however, unlike other inanimate objects, animals are emotional and intelligent beings who also deserve dignity and respect. Sometimes animals are killed without reason, which violates their right to life. Some of them, including chickens, pigs and cows, do not see outdoors except on their way to slaughterhouses, which violates their right to liberty. Business has been cited as justification, but mistreatment should be stopped at any cost by way of minimising the use of animals for industrial purposes and reducing their pain and suffering during this process. Available laws focus on the right to life of animals, while other rights, including the right to liberty, dignity and health, are ignored. While animals are emotional and intelligent beings, they are also entitled to all other rights associated with them, just like humans. Therefore, it is imperative that all other rights available for animals should also be protected. The paper argues that animals possess certain rights that are available to human beings and also intends to focus on the rights of animals on the basis of their emotional and intelligent characteristics using doctrinal and socio-legal research methodology. This paper further provides a comprehensive framework for the rights of animals that are ignored under available laws and to also suggest possible measures to implement the same.